SPECIFIC CHARACTERISTICS OF TEACHING IN "MUSIC CULTURE" LESSONS (IN THE EXAMPLE OF PRIMARY CLASSES) - Pardayev S.A. (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In this article, in the "Music culture" lessons of general secondary schools, the students' love for our national music art, the perfect understanding of music, the breathing of singing, diction Concepts regarding the method of teaching the correct execution, education of the voice range and the development of the sound production apparatus and articulation are explained. Information is provided on teaching students to be creative from school age, forming their independent improvisation (imagination) skills, and developing a methodology for organizing musical education.